GAMBARAN JUMLAH TROMBOSIT PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS TARUMANAGARA ANGKATAN 2012-2016 DENGAN OBESITAS - Patterson, Daniel Albar R; Dewi, Sari Mariyati (Ebers Papyrus, 2021)
Obesity is the condition that can adversely affect health especially on the cardiovascular system. The lack of activity as a result of advances in technology and service system today causes an increase obesity occurs in people more than 18 years old. Based on fat distributed, obesity divided into central obesity and peripheral obesity. Central obesity is more at risk of an inflammatory process that is the basis of atherosclerosis. The high production of cytokines TNF? and IL-6 cytokines can affect the process of megakaryocytopoiesis and platelet activation so that can increase in the number of platelets. In previous study, it was found a correlation between the platelet count and obesity in Korean adolescents. In Indonesia, there was no data. Medical students of Universitas Tarumanagara are also at risk of obesity, the large number of task and materials that need to be studied, makes the students less physical activity. This study was cross-sectional descriptive method to decide an increase in platelets counts in obese students as a sign of an inflammatory process.  There was 54 respondents with obesity that obtained by non-random consecutive sampling. Results: base on nutritional status, most respondents (66,7%) were obese II with female higher that man, contrast with obesity I group (male, 55%.) Base on platelet count, all respondents have normal platelet count but the average of platelet count higher in obesity II group.